Putative antinociceptive action of nitric oxide in the caudal part of the spinal trigeminal nucleus during chronic carrageenan-induced arthritis in the rat temporomandibular joint - Tesser-Viscaino, Silvia A.; Denadai-Souza, Alexandre; Teixeira, Simone A.; Ervolino, Edilson [UNESP]; Cruz-Rizzolo, Roelf J.; Costa, Soraia K.; Muscara, Marcelo N.; Casatti, Cláudio Aparecido [UNESP] (Elsevier B.V., 2009)
In order to investigate a putative role for nitric oxide (NO) in the central nociceptive processing following carrageenan-induced arthritis in the rat temporomandibular joint (TMJ), we analyzed the immunoreactivity, gene expression and activity of nitric oxide synthases (NOS) in the caudal part of the spinal trigeminal nucleus (Sp5C) during the acute (24 h), chronic (15 days) and chronic-active (14 days-24 h) arthritis. In addition, evaluation of head-withdrawal threshold was carried out in all phases of arthritis under chronic inhibition of nNOS with the selective inhibitor 7-nitroindazole (7-NI). Neurons with nNOS-like immunoreactivity (nNOS-LI) were concentrated mainly in the lamina II of the Sp5C, showing no significant statistical difference during arthritis. Only a discrete percentage of nNOS-LI neurons expressed Fos immunoreactivity. The mRNA expression for both nNOS and endothelial nitric oxide synthases (eNOS) presented no noticeable differences among the groups. No expression of inducible nitric oxide synthase (iNOS) was detected in the Sp5C by either immunohistochemistry or reverse-transcription polymerase chain reaction (RTPCR). Ca(2+)-dependent NOS activity in the ipsilateral Sp5C was significantly higher (108.3 +/- 49.2%; P<0.01) in animals during the chronic arthritis. Interestingly, this increased activity was completely abolished 24 h later, in the chronic-active arthritis. Finally, head-withdrawal threshold decreased significantly in the chronic arthritis in animals under 7-NI chronic inhibition. In conclusion, nNOS immunoreactivity and mRNA expression are stable in the Sp5C during TMJ arthritis evolution, but its activity significantly increases in the chronic-phases supporting an antinociceptive role of the nNOS as evidenced by pain threshold experiment. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Arthritis; Nitric oxide synthase; Spinal trigeminal nucleus; Temporomandibular joint